Saudi Nursing Students Experience of Distance Learning (e-learning) During COVID-19 2020 Pandemic Outbreak at KSAU-HS - Barnawi, Najla A.; Al-Mutair, Angham; Al-Ghadeer, Hind (International Journal of Innovative Research in Medical Science, 2021)
Objectives: This study aims to assess the experience of the full Distance Learning approach among nursing students during COVID-19 Outbreak at KSAU-HS in the three regions (Riyadh, Jeddah, and Al-Ahsa). The study covers the following objectives; measuring the students’ level of satisfaction, perception, and interest in integrating Distance Learning, their learning needs accomplishments; and determine the association between the student’s level of satisfaction, perception/interest in integrating Distance Learning, and learning needs accomplishments. Methods: A cross-sectional study was conducted among 800 nursing students in the CON campuses. The validated 5-Lickert scale DSLLA, was used to assess the student’s demographical data, satisfaction, and learning achievements. The r values were calculated to examine the correlation between the students' satisfaction and other study variables. Results: The majority of the participants were satisfied 70.9% and 90% were toward integrating the e-learning and 89.4% reported that they meet their learning needs. There was a statistically significant relationship between the participants’ satisfaction with learning styles (r=0.305, P= 0.000) and their learning needs achievements (r=.600, P=0.000). Conclusion: Integrating the companied learning style is the best learning option to deliver the pedagogy process within the Nursing curricula; however, the full distance learning approach is an effective tool on delivering the pedagogy process mainly during COVID-19.